Le rôle des collocations et des locutions dans les notes des joueurs de football - Cerovšek, Mateja (Vestnik za tuje jezike, 2018)
The presence of phraseological units in a sports text is not arbitrary. Furthermore, collocations and idiomatic expressions, fixed by form, meaning or use, also appear in very particular types of sports commentary, for instance in the football player analysis, where they take on different roles. The pragmatic aspect of the football terminological expressions ensures communication within this specific domain. The phraseological units, however, also have a stylistic role. Firstly, the journalistic expressions announce the type of text, in this case the media sports discourse. Secondly, many expressions are included with the sole purpose of making the otherwise technical text richer.
Keywords: francoščina; kolokacije; nogomet; stalne besedne zveze; šport; športni komentar